Ecology of the non-native snail Sinotaia cf quadrata (Caenogastropoda: Viviparidae) - Ferreira, Ana Clara (2017)
Sinotaia quadrata is a snail native from Asia recorded for the first time in South America in 2009 in centralArgentina. In 2015, this species was also found in a lowland stream with different water qualities. Our aimswere to contribute to the knowledge of its population ecology and to compare the individuals from the twolocations anatomically. Snails were searched at 6 sites, where physicochemical and hydraulic parameters were measured. Biological samples were also taken at two sites (S3 and S4) to study the population traits of S. cf quadrata (density, sizestructure, fecundity and sex ratio) and to assess the water quality throughmacroinvertebrates’ biological indices (richness, diversity and IBPamp). Physicochemical and biologicalparameters allowed us classifying sites as “moderately polluted” (S3) and “heavily polluted” (S4). At S4,the population showed a lower density, larger individuals, higher fecundity and a scarce representation ofyoung snails. The differences observed in the radula and mantle border of snails from the two geographicalregions might be attributed to environmental differences. We conclude that this species is tolerant to a widerange of environmental variables which, along with its high fecundity and morphological plasticity, couldallow this species to colonize neighbor streams.